Isolation of feline islets of Langerhans by selective osmotic shock produces glucose responsive islets - Porter, Lauren T.; Adin, Christopher A.; Crews, Chiquitha D.; Mott, Jocelyn; Gilor, Chen (Frontiers in Veterinary Science, 2024)
Introduction Pancreatic islet isolation is essential for studying islet physiology, pathology, and transplantation, and feline islets could be an important model for human type II diabetes mellitus (T2D). Traditional isolation methods utilizing collagenases inflict damage and, in cats, may contribute to the difficulty in generating functional islets, as demonstrated by glucose-stimulated insulin secretion (GSIS). GLUT2 expression in β cells may allow for adaptation to hyperosmolar glucose solutions while exocrine tissue is selectively disrupted. Methods Here we developed a protocol for selective osmotic shock (SOS) for feline islet isolation and evaluated the effect of different hyperosmolar glucose concentrations (300 mmol/L and 600 mmol/L) and incubation times (20 min and 40 min) on purity, morphology, yield, and GSIS. Results Across protocol treatments, islet yield was moderate and morphology excellent. The treatment of 600 mmol/L glucose solution with 20 min incubation resulted in the highest stimulation index by GSIS. Discussion Glucose responsiveness was demonstrated, permitting future in vitro studies. This research opens avenues for understanding feline islet function and transplantation possibilities and enables an additional islet model for T2D.